Status of antimicrobial stewardship programmes in Nigerian tertiary healthcare facilities: Findings and implications. (June 2019) - Fadare, Joseph O.; Ogunleye, Olayinka; Iliyasu, Garba; Adeoti, Adekunle; Schellack, Natalie; Engler, Deirdre; Massele, Amos; Godman, Brian
Highlights: Antimicrobial resistance (AMR) is a growing concern, especially in sub-Saharan Africa. Antimicrobial stewardship programmes (ASPs) can reduce AMR, but little is known about them in Nigeria. Only 24% of tertiary hospitals had an ASP, increasing to 35% with formalised structures and teams for stewardship. Less than 25% have specific treatment recommendations, and only 12% have a formal procedure for reviewing appropriateness. Antimicrobial susceptibility reports for the previous year were available in 18% of facilities, and 6% monitor utilisation. The Nigerian Ministry of Health and other key stakeholders need to address the lack of ASPs to improve antimicrobial use. Abstract: Objectives: The problem of antimicrobial resistance (AMR) is increasing worldwide, with health-related and economic consequences. This is a concern in Africa, including Nigeria, the most populous country in Africa, with its high rates of infectious diseases. Approaches to reducing AMR include instigating antimicrobial stewardship programmes (ASPs) in hospitals. Currently, no information is available regarding the extent of ASPs in Nigerian hospitals. Consequently, the objective was to address this starting in tertiary hospitals. Methods: This was a cross-sectional, questionnaire-based study among tertiary healthcare facilities. Tertiary hospitals were chosen initially since if there are concerns in these training hospitals, such concerns will likely to be exacerbated in other hospitals. Results: Completed questionnaires were received from 17 of 25 tertiary healthcare facilities across five of the six geopolitical regions of Nigeria. Ten (59%), four (24%), two (12%) and one (6%) respondents were in internal medicine, infectious diseases, medical microbiology and clinical pharmacology, respectively. Only six healthcare facilities (35%) had a formal organisational structure and a team responsible for ASP. Facility-specific treatment recommendations, based on local AMR patterns, were available in only four facilities (24%). Policies on approval for prescribing specified antimicrobials and formal procedures for reviewing their appropriateness after 48 h were present in only two facilities (12%). A cumulative antimicrobial susceptibility report for the previous year was available in only two facilities (12%), and only one facility routinely monitored antimicrobial use. Conclusion: Significant inadequacies in the availability of ASPs were observed. This needs to be urgently addressed to reduce AMR rates in Nigeria.